2017
DOI: 10.5123/s2176-62232017000100003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da atividade antibacteriana dos monoterpenos timol e carvacrol contra cepas de Escherichia coli produtoras de β-lactamases de amplo espectro

Abstract: RESUMOOBJETIVOS: Estudar a atividade antimicrobiana dos fitoconstituintes timol e carvacrol contras cepas de Escherichia coli produtoras de β-lactamases de amplo espectro (ESBL) e determinar a concentração inibitória mínima (CIM) do timol e do carvacrol. MATERIAIS E MÉTODOS: Os experimentos foram realizados no Laboratório de Microbiologia (J11) no Centro de Educação e Saúde da Universidade Federal de Campina Grande, estado da Paraíba, Brasil. Para a determinação da CIM dos fitoconstituintes selecionados, foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
5
0
7
Order By: Relevance
“…In vitro studies have demonstrated the antimicrobial action of carvacrol against V. parahaemolyticus, S. aureus and Pseudomonas fluorescens which presented a MIC of 0.5, 0.125 and 0.5 mg mL -1 , respectively (Fang et al, 2019). In another study, carvacrol was evaluated against other microorganisms, such as strains of E. coli, showing a MIC of 0.064 mg mL -1 , and S. typhimurium, showing a MIC of carvacrol of 0.12 mg mL -1 (Lemos et al, 2017;Lima et al, 2017). In addition, thyme essential oil (T. vulgaris), containing 60% carvacrol, was evaluated against V. vulnificus, Vibrio fluvialis and V. parahaemolyticus with a MIC of carvacrol of 0.156 mg mL -1 ,…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated the antimicrobial action of carvacrol against V. parahaemolyticus, S. aureus and Pseudomonas fluorescens which presented a MIC of 0.5, 0.125 and 0.5 mg mL -1 , respectively (Fang et al, 2019). In another study, carvacrol was evaluated against other microorganisms, such as strains of E. coli, showing a MIC of 0.064 mg mL -1 , and S. typhimurium, showing a MIC of carvacrol of 0.12 mg mL -1 (Lemos et al, 2017;Lima et al, 2017). In addition, thyme essential oil (T. vulgaris), containing 60% carvacrol, was evaluated against V. vulnificus, Vibrio fluvialis and V. parahaemolyticus with a MIC of carvacrol of 0.156 mg mL -1 ,…”
Section: Discussionmentioning
confidence: 99%
“…O. Berg, followed by compounds classified as organic acids and alcohols [ 12 ]. It is known that the essential jabuticaba oil contains terpenes, such as α-pinene, β-pinene, 1,8-cineole, α-terpineol, and β-caryophyllene, known for their antibacterial and anti-inflammatory actions, suggesting that the same volatile compounds present in the fruit aroma are indicative of endogenous levels and potential bioactive action [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As beta-lactamases são enzimas capazes de hidrolisar o anel beta-lactâmico (Figura 2a) de antibióticos como, penicilinas, cefalosporinas, carbepenêmicos e monobactâmicos. Estas enzimas são codificadas nos plasmídeos, transpósons e íntegrons, sendo elementos capazes de carregar o gene de resistência, transmitindo horizontalmente para outras bactérias (Lima, Lima, Calvacanti, Santos & Lima, 2017).…”
Section: Metodologiaunclassified